Key Factors Influencing Rice Farmers' Decisions: Animal Power vs. Tractors in Kalibombong Village, Banjarnegara, Indonesia - Rozaki Zuhud; Indri Yustika; Indardi; Wulandari Retno; Triyono; Rahmawati Nur; Ardila Riska Aula (BIO Web of Conferences)
Land management in paddy farming can be done traditionally with animal power or modernly with tractors. Tractors facilitate land management but are not accessible to all farmers. This study investigates paddy farmers' motivation to use animal power and tractors, using the ERG motivation theory (Existence, Growth, and Relatedness). A descriptive, quantitative approach was applied to 60 farmers. Findings show that motivation to use tractors is very high in the Existence category, and moderate in Relatedness and Growth categories. Motivation to use animal power is high in Existence and moderate in Relatedness and Growth. Age affects Existence motivation to use tractors at a very low level, while education, income, innovation openness, risk-taking, and cosmopolitanism relate to Relatedness at a very low level. Land area, innovation openness, and risk-taking relate to Existence motivation for animal power users at a low level. Future orientation is linked to Growth motivation at a low level. Increasing tractor use efficiency can boost production, but challenges like capital and land tenure limit adoption.